Biochemical Patterns of Cardio-renal Biomarkers in Serum and Vitreous Humor of Rabbits after Chronic CO Exposure - Agoro Eni-yimini Solomon; Wankasi Mieebi Martin; Ombor Jerry Okpoubolokemi (Annals of Environmental Science and Toxicology - Peertechz Publications, 2019)
Carbon monoxide (CO) is a colorless gas that can cause cellular damage in exposed hosts depending on the levels inhaled. There is an increase in idiopathic diseases without a known cause. In Nigeria, this has led to a call for profiling of CO, a gas routinely inhaled by its population. This study was designed to assess the effect of chronic CO inhalation on vitreous and serum cardiorenal biochemical parameters. A total of twenty rabbits were divided into four groups. With the exception of control rabbits (air only), others were exposed daily to 200 ppm CO for 30 min for 10, 20, or 30 days. Five (5) rabbits constituted each of the four groups. At the 30 minutes after the final exposure, rabbits were euthanized mechanically and their vitreous humor and cardiac blood extracted using standard procedures. Serum and vitreous humor extracted were analyzed using ion selective electrode and enzymatic methods. The serum chemistry data revealed that pH, Na, non-ionized calcium (nCa), ionized calcium (Ca), total calcium (TCa), creatinine, lactate dehydrogenase (LDH), and creatine kinase concentrations were significantly raised (p< 0.05) as the duration of exposure increased. In contrast, uric acid (UA) concentrations were significantly decreased. The vitreous humor chemistry data revealed significant increases in creatinine, urea, LDH, and CK concentrations, whereas pH and concentrations of potassium, TCa, nCa, Ca, and UA were significantly decreased (p< 0.05). Thus, it may be possible to assess chronic CO poisoning by evaluating one or more biochemical alterations in the serum and vitreous humour.